Flexibilidade em edificações residenciais: diretrizes de projeto e análise da aplicação no mercado imobiliário brasileiro - Legonde, Cláudia Kraemer (Universidade do Vale do Rio dos Sinos, 2017)
The rinsing of unpredictability over time, changes in people's way of life, globalization and the development of technology have required residential housing capable of adapting to such transformations. Flexibility in architecture is about the ability to adapt to the needs or requirements of users in a rational way. The current scenario of limited, conventional, and repetitive space arrangement, offered by real estate market, forces users to modify their homes through demolitions, renovations, and consequent environmental losses. In view of this, it is up to the designer to use flexibility as a strategy to ensure a higher quality architecture project, proposing the application of new materials and constructive solutions. The main objective of this work is to identify design guidelines that promote flexibility in residential buildings, as well as to analyze their application in the real estate market. The research method used had as reference a bibliographic review for a better understanding of the subject. The proposed guidelines were detailed and exemplified, divided into the following items: independent structure, structural modulation, free plan, light internal partitions, movable partitions, free facade, service cores, installation shafts, recessed ceiling and raised floor. With the purpose of exposing the practical application of flexibility, we selected five flexible residential multifamily buildings currently offered in the Brazilian real estate market. These buildings were analyzed for the flexibility strategies used and the existing types of flexibility presented by researched authors. As a result , it is observed that practically all proposed project guidelines were used in some way in the analyzed buildings, promoting several types of flexibility. In order for flexibility to be achieved, these guidelines must be combined to form a flexible system, and must be inserted in the design phase of the building, which has the lowest costs and the greatest possibilities for intervention. The use of flexibility in the architecture brings satisfaction to the users and the increase in the performance and the useful life of the buildings, thus collaborating with the sustainability in the civil construction.
Keywords: Flexibilidade; Edificações residenciais; Mercado imobiliário; Sustentabilidade; Flexibility; Residential buildings; Real estate market; Sustainability; ACCNPQ::Ciências Sociais Aplicadas::Arquitetura e Urbanismo